Effect of Competency and Emotional Intelligence on Audit Quality - Satriadi Sukri; S. Salju; Suardi M. Anwar; S. Sapar (PT Mattawang Mediatama Solution, 2022)
The purpose of this study was to describe and analyze the effect of competence and emotional intelligence on audit quality at the North Luwu Regency Inspectorate. Data analysis used variant-based SEM (VB SEM) with the help of Smart PLS software version 3.3. The results of the study indicate that competence has an effect on audit quality by 0.935 units with a t count value of 16,582 > t table = 1.90. or the P Value of 0.000 < 0.05. Emotional intelligence has no effect on audit quality of 0.055 units with a value of t count = 0.847 < t table = 1.900 or a P Value of 0.397 > 0.05. The joint influence of competence and emotional intelligence on audit quality is 96.3% while 3.7% is influenced by other variables not examined in this study.